Communicate with mastery : how to speak with conviction and write for impact - Schramm, J. D., 1964-; Levy, Kara, 1981- (Wiley, 2020)
"Approaching Mastery in Business Communication: a guide for leaders to speak and write with influence. This book will provide readers with a rich treasure of frameworks and tools for leadership communication as developed and taught over the past decade at Stanford's Graduate School of Business. Designed for the business leader on the go the book will provide quick access to helpful approaches to vexing communication problems leaders face today in speaking and writing to various audiences. It will address the pain point that leaders are often selected for their technical skills, but advance because of their communication skills. Projects often fail not because of the vision, but in the articulation of that vision. Promising start-ups wither without funding, while less viable ventures are funded, simply due to the strength of the communicators. This book will place in leaders' hands the exact frameworks and strategies developed at one of the world's top business schools. While firmly grounded in proven approaches, the book will be designed in a practical and accessible style for easy reference and use"--